Discourse about evasion and permanence: tracking controversies in the document of the TCU audit report/2013 - Carmo, Gerson Tavares do (2023)
The low academic performance of students and the high evasion rates in Federal Institutes had their visibility assumed in the Audit Report document (TC 026.062/2011-9) prepared by Tribunal de Contas da União (TCU) in 2013. The document is about a supervision of the performance of Federal Institutes regarding measures to combat evasion, among other aspects, in which these educational institutions were required to propose an action plan to overcome evasion and retention. In the face of this scenario, from the perspective of Document Analysis, this article aims at analyzing the discourse on school evasion in the TCU Report's document and, more specifically, in the documents that relate to it, in order to highlight the networks of discursive practices that led to the idea that it is necessary to turn the evasion theories into institutional practices which aim at permanence, bearing in mind that the studies about evasion, although they are advantageous for their diagnostic nature, have little practical effectiveness in the intervention potential of the institution. As a result, it was observed that the underlying questions of the evasion perspective, such as conceptual and methodological precariousness, comprehension by false causality and cost-benefit ratio, considered here as "idols" of thought, were deconstructed throughout the documentary events, promoting a transition from the studies of evasion to the studies of permanence.